Single-crystal lithium manganese iron phosphate positive electrode material and preparation method thereof

CN122959832APending Publication Date: 2026-10-23SHANXI TEWASHI ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611036541.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]但现有磷酸锰铁锂材料规模化应用存在两大固有晶格缺陷,严重制约其商业化落地

Benefits of technology

[0017]相较于现有传统磷酸锰铁锂及其制备工艺,本发明通过晶面定向调控、晶格梯度铌掺杂预存压应力、原位Li3PO4-碳双相复合包覆三重协同改性,从晶体生长、体相晶格、颗粒界面三个维度同步解决单晶磷酸锰铁锂倍率差、循环衰减严重、晶格膨胀破碎等核心痛点,具备如下突出技术优势:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a single-crystal manganese iron lithium phosphate positive electrode material and a preparation method thereof, and belongs to the technical field of lithium batteries. The application adopts a ternary crystal face capping agent solvothermal synthesis (010) to preferentially expose a precursor; introduces a niobium source through segmented ball milling, constructs a crystal lattice pre-stress through segmented calcination and rapid cooling; and finally, the application is heat-treated with ammonium dihydrogen phosphate and sucrose to generate a Li3PO4-carbon composite coating layer in situ. The application can improve the proportion of active crystal faces, offset the lattice expansion, and construct a double-conductive network. The obtained material has excellent rate capability and cycle performance, and the process is easy to be industrialized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium battery technology, specifically to a single-crystal lithium manganese iron phosphate cathode material and its preparation method. Background Technology

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, and no memory effect, have been widely used in new energy vehicles, energy storage power stations, and portable electronic devices. Cathode materials, as the core components determining the energy density, cycle stability, and safety performance of lithium batteries, are a key breakthrough for technological iteration in the industry. Lithium manganese iron phosphate (LMFP) combines the high safety and low cost of lithium iron phosphate with the high voltage and high specific capacity of lithium manganese phosphate. Its theoretical discharge specific capacity can reach over 170 mAh / g, and its operating voltage is 0.3-0.4 V higher than that of lithium iron phosphate, significantly improving the energy density of battery systems. It is considered a core candidate material for the next generation of low-cost power and energy storage lithium battery cathodes.

[0003] However, the large-scale application of existing lithium manganese iron phosphate (LMFP) materials suffers from two inherent lattice defects, severely hindering their commercialization. First, the lattice deformation during the lithium insertion / extraction process of LMFP crystals exhibits strong directionality. The lattice stretching rate of the (010) crystal plane, a dedicated channel for lithium ion transport, can reach 5-7%. Polycrystalline secondary particles prepared by traditional solid-state and hydrothermal methods are composed of a large agglomeration of randomly oriented primary nanocrystals. During charge-discharge cycles, the lattice expansion of different grains causes mutual compression, continuously generating microcracks within the particles. This not only causes desorption of the active material from the conductive network but also accelerates the dissolution of manganese ions, damaging the crystal framework and ultimately leading to rapid capacity decay. Second, LMFPs only exhibit one-dimensional Li+ along the (010) crystal orientation. + Migration channels, disordered grain orientation of polycrystalline materials, a large number of particles exposed low-activity (100) and (001) crystal planes, lithium-ion diffusion resistance increased significantly, severe polarization under high-rate charge and discharge, and precipitous drop in discharge capacity, making it difficult to meet the needs of fast-charging power batteries.

[0004] To alleviate the aforementioned shortcomings of polycrystalline materials, existing technologies generally adopt a single-crystal preparation approach, reducing microcrack formation by eliminating grain boundaries. However, the current single-crystal lithium manganese iron phosphate preparation process still has significant technical shortcomings: First, conventional synthesis systems lack directional crystal plane control methods, single-crystal particle growth lacks preferred orientation, and the finished product still exposes a large number of (100) and (001) inert crystal planes, resulting in limited improvement in ion transport efficiency. The rate performance of some single-crystal samples is even inferior to that of modified polycrystalline materials. Second, existing surface carbon coating processes simply deposit amorphous carbon layers, which can only improve electronic conductivity but cannot improve the lithium-ion interface conduction rate. The carbon layer has poor contact stability with the crystal interface and is prone to peeling and failure during cycling.

[0005] Therefore, how to simultaneously achieve the selective exposure of highly active (010) crystal planes of single crystal particles, the pre-set compressive stress field inside the lattice to offset the volume expansion during charging and discharging, and the construction of a composite coating network on the single crystal surface that combines ion conductivity and electronic conductivity are key technical challenges that urgently need to be overcome in the field of lithium manganese iron phosphate cathode materials. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a single-crystal lithium manganese iron phosphate cathode material and its preparation method, which can increase the proportion of active crystal faces, offset lattice expansion, construct a dual conductive network, and the resulting material has excellent rate capability and cycle performance, and the process is easy to industrialize.

[0007] The technical solution of this invention is as follows: On one hand, the present invention provides a method for preparing a single-crystal lithium manganese iron phosphate cathode material, comprising the following steps: S1 dissolves manganese, iron, and phosphorus sources with crystal facet end-capping agents in a polyol solvent and reacts them in a solvothermal manner at 180-200℃ for 18-24 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, filtered, washed, and dried to obtain precursor single crystal particles with (010) crystal facet preferential exposure characteristics. Among them, the crystal facet end-capping agents are oleylamine, hexadecyltrimethylammonium bromide, and ammonium fluoride. S2 The precursor obtained in step S1 is mixed with lithium source and niobium source by ball milling. First, it is mixed at a speed of 240-250 rpm for 1-2 hours, and then at a speed of 600-620 rpm for 2-3 hours. S3 Calcine the mixture obtained in step S2 under a weak reducing atmosphere. First, heat the mixture to 500-520℃ at a rate of 25-30℃ / min and hold it for 1-2 hours. Then, heat the mixture to 700-720℃ at a rate of 5-8℃ / min and hold it for 5-6 hours. After the process, cool the mixture to room temperature at a rate of ≥50℃ / min. S4. The material obtained in step S3 is mixed with ammonium dihydrogen phosphate and an organic carbon source, and then heat-treated at 600-620℃ for 1-3 hours under an inert atmosphere to transform the single crystal surface in situ into a composite coating layer of Li3PO4 nanocrystals and amorphous carbon, thus obtaining a single crystal lithium manganese iron phosphate cathode material.

[0008] Preferably, in step S1, the amount of manganese source, iron source and phosphorus source added satisfies the molar ratio of Mn, Fe and P as (0.6-0.8):(0.2-0.35):1.

[0009] Preferably, in step S1, the amount of oleylamine added is 2-4% of the total mass of manganese source, iron source and phosphorus source, the amount of hexadecyltrimethylammonium bromide added is 1-3% of the total mass of manganese source, iron source and phosphorus source, and the amount of ammonium fluoride added is 0.5-1% of the total mass of manganese source, iron source and phosphorus source.

[0010] Preferably, in step S1, the polyol solvent is ethylene glycol.

[0011] Preferably, in step S2, the niobium source is niobium oxide or ammonium niobium oxalate.

[0012] Preferably, in step S2, the precursor is mixed with the lithium source and the niobium source at a molar ratio of Li:(Mn+Fe+Nb)=1.05:1, wherein the niobium element accounts for 1-2% of the total molar amount of the metal elements.

[0013] Preferably, in step S3, the weakly reducing atmosphere is a mixture of Ar and H2 with a volume ratio of 95:5.

[0014] Preferably, in step S4, the organic carbon source is sucrose.

[0015] Preferably, in step S4, the amount of ammonium dihydrogen phosphate added is 2-4% of the mass of the material obtained in step S3, and the amount of organic carbon source added is 5-8% of the mass of the material obtained in step S3.

[0016] On the other hand, the present invention provides a single-crystal lithium manganese iron phosphate cathode material, which is prepared by the above-described method for preparing single-crystal lithium manganese iron phosphate cathode material.

[0017] Compared to existing traditional lithium manganese iron phosphate and its preparation process, this invention addresses the core pain points of single-crystal lithium manganese iron phosphate, such as low rate capability, severe cycle decay, and lattice expansion and breakage, through a triple synergistic modification of crystal plane orientation control, niobium doping pre-stored compressive stress in the crystal gradient, and in-situ Li3PO4-carbon dual-phase composite coating. This simultaneously solves these issues from three dimensions: crystal growth, bulk lattice, and particle interface. It possesses the following outstanding technical advantages: 1. In the solvothermal precursor preparation stage, this invention combines oleylamine, CTAB, and ammonium fluoride as ternary crystal facet end-capping agents to synergistically regulate the thermodynamics and kinetics of crystal growth through temperature field control. This selectively inhibits the growth of inert (100) and (001) crystal faces, forces single crystal particles to preferentially grow along the

[010] crystal orientation of the one-dimensional lithium-ion transport channel, significantly increases the exposure ratio of the (010) highly active crystal facet, and opens up the Li-ion transport channel from the crystal origin. + High-speed diffusion channel. Compared with ordinary single-crystal materials without crystal-faceted end-capping agents, the lithium-ion diffusion coefficient of the product of this invention is significantly improved, and the discharge capacity at a high rate of 10C can reach more than 150mAh / g. It has low polarization and low capacity decay at high rates, which is suitable for the fast charging requirements of power batteries.

[0018] 2. This invention employs a segmented variable-speed ball milling process combined with high-temperature rapid quenching to achieve Nb 5+ A gradient doping structure in which high-valence cations are highly enriched on the surface of single-crystal particles and have low content inside; Nb 5+Due to the difference in ionic radius between the ions and the matrix metal ions, rapid cooling after high-temperature calcination can permanently freeze the lattice gradient compressive stress within the crystal. During battery charging and discharging, the expansion stress generated by lithium insertion / extraction in the lattice can be offset by the pre-stored compressive stress, significantly reducing the anisotropic deformation of the (010) crystal plane, alleviating the Jahn-Teller effect, reducing microcrack formation at its source, and inhibiting manganese ion dissolution. After 2000 long cycles, the capacity retention rate can reach over 93%, far superior to the comparative sample prepared by stress-free conditioning and natural cooling.

[0019] 3. In the post-treatment heat treatment stage, ammonium dihydrogen phosphate is introduced, which can generate Li3PO4 fast ion conductor nanocrystals in situ with the excess lithium source on the single crystal surface. Combined with the continuous amorphous carbon layer formed by sucrose pyrolysis, a point-to-surface dual continuous percolation coating structure of "ion-conducting nano-islands + electron-conducting carbon network" is constructed. Li3PO4 has excellent lithium-ion conductivity, which makes up for the lack of ion conductivity of pure carbon coating; the outer carbon layer ensures rapid electron transport between particles, while isolating the electrolyte from direct contact with the single crystal matrix, further reducing transition metal dissolution, improving interfacial structural stability, and achieving the dual benefits of rate performance and cycle stability.

[0020] 4. The monocrystalline lithium manganese iron phosphate prepared by this invention has multiple advantages, including no grain boundaries, highly active crystal faces, stress-buffered lattice, and two-phase conductive coating. The discharge specific capacity can reach more than 166 mAh / g at a low rate of 0.1C. At the same time, it inherits the inherent high thermal stability and safety characteristics of lithium manganese iron phosphate, and takes into account high energy density, excellent fast charging capability and ultra-long cycle life. It can be adapted to various application scenarios such as power batteries for new energy passenger vehicles and large-scale energy storage power stations. Detailed Implementation

[0021] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0022] Example 1 The preparation method of the single-crystal lithium manganese iron phosphate cathode material in this embodiment includes the following steps: S1: MnSO4·H2O, FeSO4·7H2O, and H3PO4 were dissolved in ethylene glycol at a molar ratio of Mn:Fe:P = 0.7:0.285:1. Oleylamine (2% by mass of the total MnSO4·H2O, FeSO4·7H2O, and H3PO4), CTAB (1% by mass), and NH4F (0.5% by mass) were added as crystal facet sealing agents. The resulting mixed solution was transferred to a hydrothermal reactor and reacted at 200℃ for 18 h. After the reaction, the mixture was naturally cooled to room temperature, filtered, washed, and dried to obtain precursor single crystal particles with preferred exposure of the (010) crystal facet.

[0023] S2: The precursor obtained in step S1 is mixed with Li2CO3 and Nb2O5 at a molar ratio of Li:(Mn+Fe+Nb)=1.05:1, wherein Nb accounts for 1.5% of the total molar amount of the metal elements. The mixture is placed in a high-energy ball mill and mixed at a low speed of 250 rpm for 1 hour, followed by a high speed of 600 rpm for 2 hours. The difference between mechanical force-induced surface amorphization and bulk diffusion is utilized to allow Nb to... 5+ The concentration of particles on the surface is much higher than that in the core area.

[0024] S3: The mixture obtained in step S2 is placed in a tube furnace and subjected to a non-equilibrium rapid heating-segmented holding process under a weakly reducing atmosphere of Ar / H2 = 95:5: The temperature is rapidly increased to 520℃ at a rate of 25℃ / min and held for 1.5 hours; then increased to 720℃ at a rate of 5℃ / min and held for 6 hours. After the holding period, liquid nitrogen-assisted air cooling is used to lower the temperature to room temperature at an extremely rapid cooling rate of approximately 60℃ / min, thus reducing the Nb content at high temperatures. 5+ The lattice compressive stress induced by doping is "frozen" inside the single crystal.

[0025] S4: The material obtained in step S3 is mixed evenly with 2 wt.% NH4H2PO4 and 5 wt.% sucrose, and heat-treated at 600℃ for 1 hour under N2 atmosphere. During this process, the Li remaining on the single crystal surface reacts with NH4H2PO4 to transform into Li3PO4 nanocrystals in situ, while the sucrose decomposes into amorphous carbon. The two grow conformally to form a composite coating layer. After natural cooling, the target product is obtained.

[0026] Example 2 The preparation method of the single-crystal lithium manganese iron phosphate cathode material in this embodiment includes the following steps: S1: MnSO4·H2O, FeSO4·7H2O, and H3PO4 were dissolved in ethylene glycol at a molar ratio of Mn:Fe:P = 0.7:0.28:1. Oleylamine (2% by mass of the total MnSO4·H2O, FeSO4·7H2O, and H3PO4), CTAB (1% by mass), and NH4F (0.5% by mass) were added as crystal facet sealing agents. The resulting mixed solution was transferred to a hydrothermal reactor and reacted at 200℃ for 18 h. After the reaction, the mixture was naturally cooled to room temperature, filtered, washed, and dried to obtain precursor single crystal particles with preferred exposure of the (010) crystal facet.

[0027] S2: The precursor obtained in step S1 is mixed with Li2CO3 and Nb2O5 at a molar ratio of Li:(Mn+Fe+Nb)=1.05:1, wherein Nb accounts for 2% of the total molar amount of the metal elements. The mixture is placed in a high-energy ball mill and mixed at a low speed of 250 rpm for 1 hour, followed by a high speed of 600 rpm for 2 hours. The difference between mechanical force-induced surface amorphization and bulk diffusion is utilized to allow Nb to... 5+ The concentration of particles on the surface is much higher than that in the core area.

[0028] S3: The mixture obtained in step S2 is placed in a tube furnace and subjected to a non-equilibrium rapid heating-segmented holding process under a weakly reducing atmosphere of Ar / H2 = 95:5: The temperature is rapidly increased to 520℃ at a rate of 25℃ / min and held for 1.5 hours; then increased to 700℃ at a rate of 5℃ / min and held for 6 hours. After the holding period, liquid nitrogen-assisted air cooling is used to lower the temperature to room temperature at an extremely rapid cooling rate of approximately 60℃ / min, thus reducing the Nb content at high temperatures. 5+ The lattice compressive stress induced by doping is "frozen" inside the single crystal.

[0029] S4: The material obtained in step S3 is mixed evenly with 2 wt.% NH4H2PO4 and 5 wt.% sucrose, and heat-treated at 600℃ for 1 hour under N2 atmosphere. During this process, the Li remaining on the single crystal surface reacts with NH4H2PO4 to transform into Li3PO4 nanocrystals in situ, while the sucrose decomposes into amorphous carbon. The two grow conformally to form a composite coating layer. After natural cooling, the target product is obtained.

[0030] Example 3 The preparation method of the single-crystal lithium manganese iron phosphate cathode material in this embodiment includes the following steps: S1: MnSO4·H2O, FeSO4·7H2O, and H3PO4 were dissolved in ethylene glycol at a molar ratio of Mn:Fe:P = 0.65:0.335:1. Oleylamine (2% by mass of the total MnSO4·H2O, FeSO4·7H2O, and H3PO4), CTAB (1% by mass), and NH4F (0.5% by mass) were added as crystal facet sealing agents. The resulting mixed solution was transferred to a hydrothermal reactor and reacted at 180°C for 24 hours. After the reaction, the mixture was naturally cooled to room temperature, filtered, washed, and dried to obtain precursor single crystal particles with preferred exposure of the (010) crystal facet.

[0031] S2: The precursor obtained in step S1 is mixed with Li2CO3 and Nb2O5 at a molar ratio of Li:(Mn+Fe+Nb)=1.05:1, wherein Nb accounts for 1% of the total molar amount of the metal elements. The mixture is placed in a high-energy ball mill and mixed at a low speed of 250 rpm for 1 hour, followed by a high speed of 600 rpm for 2 hours. The difference between mechanical force-induced surface amorphization and bulk diffusion is utilized to allow Nb to... 5+ The concentration of particles on the surface is much higher than that in the core area.

[0032] S3: The mixture obtained in step S2 is placed in a tube furnace and subjected to a non-equilibrium rapid heating-segmented holding process under a weakly reducing atmosphere of Ar / H2 = 95:5: The temperature is rapidly increased to 520℃ at a rate of 30℃ / min and held for 1.5 hours; then increased to 720℃ at a rate of 8℃ / min and held for 6 hours. After the holding period, liquid nitrogen-assisted air cooling is used to lower the temperature to room temperature at an extremely rapid cooling rate of approximately 60℃ / min, thus reducing the Nb content at high temperatures. 5+ The lattice compressive stress induced by doping is "frozen" inside the single crystal.

[0033] S4: The material obtained in step S3 is mixed evenly with 2 wt.% NH4H2PO4 and 5 wt.% sucrose, and heat-treated at 620℃ for 2 hours under N2 atmosphere. During this process, the Li remaining on the single crystal surface reacts with NH4H2PO4 to transform into Li3PO4 nanocrystals in situ, while the sucrose decomposes into amorphous carbon. The two grow conformally to form a composite coating layer. After natural cooling, the target product is obtained.

[0034] Comparative Example 1 The difference from Example 1 is that no crystal facet sealing agent is added in step S1.

[0035] Comparative Example 2 The difference from Example 1 is that in step S3, after the heat preservation is completed, the temperature is reduced to room temperature by natural cooling (cooling rate of about 5°C / min).

[0036] Comparative Example 3 The difference from Example 1 is that NH4H2PO4 is not added in step S4.

[0037] The electrochemical performance of the batteries assembled in Examples 1-3 and Comparative Examples 1-3 was tested, and the test results are shown in Table 1: Table 1. Electrochemical performance test results of the assembled batteries in Examples 1-3 and Comparative Examples 1-3 As shown in Table 1, compared with Example 1, Comparative Example 1 suffered from insufficient exposure of the (010) crystal face due to the lack of crystal facet end-capping agent, resulting in a significant decrease in rate performance and cycle stability. Comparative Example 2 used natural cooling, which could not effectively "freeze" the lattice compressive stress, resulting in the lattice expansion during cycling not being effectively offset. The lack of NH4H2PO4 in Comparative Example 3 led to a decrease in both rate performance and cycle stability.

Claims

1. A method for preparing a single-crystal lithium manganese iron phosphate cathode material, characterized in that, Includes the following steps: S1 dissolves manganese, iron, and phosphorus sources with crystal facet end-capping agents in a polyol solvent and reacts them in a solvothermal manner at 180-200℃ for 18-24 hours. After the reaction is completed, the mixture is naturally cooled to room temperature, filtered, washed, and dried to obtain precursor single crystal particles. The crystal facet end-capping agents are oleylamine, hexadecyltrimethylammonium bromide, and ammonium fluoride. S2 The precursor obtained in step S1 is mixed with lithium source and niobium source by ball milling. First, it is mixed at a speed of 240-250 rpm for 1-2 hours, and then at a speed of 600-620 rpm for 2-3 hours. S3 Calcine the mixture obtained in step S2 under a weak reducing atmosphere. First, heat the mixture to 500-520℃ at a rate of 25-30℃ / min and hold it for 1-2 hours. Then, heat the mixture to 700-720℃ at a rate of 5-8℃ / min and hold it for 5-6 hours. After the process, cool the mixture to room temperature at a rate of ≥50℃ / min. S4. The material obtained in step S3 is mixed with ammonium dihydrogen phosphate and an organic carbon source, and then heat-treated at 600-620℃ for 1-3 hours under an inert atmosphere to obtain a single-crystal lithium manganese iron phosphate cathode material.

2. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S1, the amount of manganese source, iron source and phosphorus source added satisfies the molar ratio of Mn, Fe and P as (0.6-0.8):(0.2-0.35):

1.

3. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S1, the amount of oleylamine added is 2-4% of the total mass of manganese, iron and phosphorus sources, the amount of hexadecyltrimethylammonium bromide added is 1-3% of the total mass of manganese, iron and phosphorus sources, and the amount of ammonium fluoride added is 0.5-1% of the total mass of manganese, iron and phosphorus sources.

4. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S1, the polyol solvent is ethylene glycol.

5. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S2, the niobium source is niobium oxide or ammonium niobium oxalate.

6. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S2, the precursor is mixed with the lithium source and niobium source at a molar ratio of Li:(Mn+Fe+Nb)=1.05:1, wherein niobium accounts for 1-2% of the total molar amount of the metal elements.

7. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S3, the weakly reducing atmosphere is a mixture of Ar and H2 with a volume ratio of 95:

5.

8. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S4, the organic carbon source is sucrose.

9. The method for preparing the single-crystal lithium manganese iron phosphate cathode material as described in claim 1, characterized in that, In step S4, the amount of ammonium dihydrogen phosphate added is 2-4% of the mass of the material obtained in step S3, and the amount of organic carbon source added is 5-8% of the mass of the material obtained in step S3.

10. A single-crystal lithium iron phosphate cathode material, characterized in that, It is prepared by the method for preparing single-crystal lithium manganese iron phosphate cathode material as described in any one of claims 1-9.